Fumigant toxicity and bioactivity of Wedelia trilobata essential oil against cowpea weevil (Callosobruchus maculatus) - Satongrod, B.; Wanna, R.; Khaengkhan, P.; Chumpawadee, T. (International Journal of Agricultural Technology, 2021)
Cowpea weevil, Callosobruchus maculatus (F.), is a storage product pest mainly controlled using synthetic insecticides. Bioactive plant essential oils can provide safer, less environmentally destructive control options. Chemical composition analysis of Wedelia trilobata essential oil was found alpha-pinene (34.96%) as the major component. Four chemical compounds: alpha-pinene, p-cymene, linalool and camphene were effective against adults of C. maculatus. The essential oil of W. trilobata was fumigant toxic at the LC50 to adults of C. maculatus with mortality at 24 h using 5304.61 μL/L air, 48 h for 2813.59 μL/L air, and 72 h for 2123.76 μL/L air. W. trilobata essential oil at a concentration of 1000 μL/L air gave optimal inhibitory effect on oviposition and adult F1 progeny emergence of C. maculatus at 73.08% and 89.13%, respectively